Impact of SARS-CoV-2 on Aerobic and Anaerobic Capacity in Professional Ice Hockey Players - Roczniok, Robert; Terbalyan, Artur; Pietraszewski, Przemysław; Mikrut, Grzegorz; Zielonka, Hanna; Stastny, Petr; Swinarew, Andrzej; Manilewska, Daria; Ornowski, Kajetan; Jabłoński, Tomasz; Lipińska, Patrycja (Journal of clinical medicine, 2025)
Background/Objectives: COVID-19 poses significant physiological challenges for athletes, particularly those engaged in high-intensity intermittent sports such as ice hockey. This study aimed to evaluate the impact of SARS-CoV-2 infection-especially symptomatic cases-on aerobic and anaerobic performance in professional ice hockey players. Methods: Fifty athletes from the Polish Hockey League were assigned to three groups: control (CG, n = 13), asymptomatic COVID-19 (NSG, n = 28), and symptomatic COVID-19 with post-infection SpO2 < 90% (WSG, n = 9). Each underwent assessments at three time points-pre-preparatory period 2020/2021, post-preparatory period 2020/2021, and pre-preparatory period 2021/2022. Aerobic capacity was measured via a progressive cycle ergometer test (VO2max, VO2 at lactate threshold [VO2Lt], minute ventilation [V'E], breathing frequency [BF], and lactate clearance rate [ΔLa]), and anaerobic capacity via a 30 s Wingate test (relative mean power). Results: Compared with CG and NSG, symptomatic athletes exhibited significant post-infection declines in VO2max (48.2 ± 2.9 vs. 56.2 ± 6.2 and 54.6 ± 3.9 mL/kg/min; p = 0.006, d = 1.56 vs. CG; p < 0.024, d = 1.79 vs. NSG) and VO2Lt (p < 0.05). Relative mean power also decreased in WSG (p < 0.05). In contrast, CG and NSG improved or maintained these metrics over the same period. Symptomatic players showed elevated BF post infection (p = 0.022, d = 1.72) and reduced V'E (p = 0.035; d = 0.83), while ΔLa was markedly lower (p = 0.0004; d = 2.86). Conclusions: SARS-CoV-2 infection, particularly symptomatic cases, can significantly impair both aerobic and anaerobic capacity in elite hockey players. Targeted recovery protocols are essential for restoring performance in affected athletes.
Keywords: ice hockey; anaerobic capacity; aerobic capacity; COVID-19